Tpeak-Tend ECG Marker in Obesity and Cardiovascular Diseases: A Comprehensive Review - Irena Dykiert; Kamila Florek; Krzysztof Kraik; Paweł Gać; Rafał Poręba; Małgorzata Poręba (Scientifica)
Globally, cardiovascular diseases are still the leading cause of death. Numerous methods are used to diagnose cardiovascular pathologies; there is still a place for straightforward and noninvasive techniques, such as electrocardiogram (ECG). Depolarization and repolarization parameters, including QT interval and its derivatives, are well studied. However, the Tpeak-Tend interval is a novel and promising ECG marker with growing evidence for its potential role in predicting malignant arrhythmias. In this review, we discuss the association between the Tpeak-Tend interval and several cardiovascular diseases, including long QT syndrome, cardiomyopathies, heart failure, myocardial infarction, and obesity, which constitutes one of the risk factors for cardiovascular diseases.